ЗНАЧЕНИЕ СОГЛАСИЯ РЕБЕНКА ПРИ УСТРОЙСТВЕ ЕГО НА ВОСПИТАНИЕ В СЕМЬЮ ПО ЗАКОНОДАТЕЛЬСТВУ УКРАИНЫ И РЕСПУБЛИКИ МОЛДОВА - Красник, Екатерина Сергеевна (SUPREMANCE OF LAW, 2018)
The article is focused on establishing the importance of a child’s consent while placing him into a family for education in accordance with the legislation of Ukraine and the Republic of Moldova. The author emphasizes on the delineation of such legal categories as “a child’s consent”, “a child’s opinion”, “a child’s desire”, on the form of the consent and desire expressed by a child. It has been concluded that the consent of a child while placing him into a family for education is legitimate and is the unilateral transaction in its legal nature. The author has suggested to amend the Family Code of Ukraine and provide that it is mandatory to obtain the consent of a child for his adoption who has reached the age of 10 years.